Impacts of causal transmission losses allocation on generation pricing for long-term contracts in Brazil - de Sa Ferreira, Rafael (Sin editorial (Montevideo, Uruguay), 2012)
The allocation of ohmic losses in the transmission system with a method that complies with the requisite of cost causality is critical for sending location-specific, efficient economic signals to transmission system users, and to incentivize the efficient use and expansion of the electricity system. In this paper, we employ a formulation of the Incremental Transmission Losses allocation method that is derived from the equations of the linearized power flow to assess the possible impacts that adopting a causal allocation method would have on generation pricing for long-term contracts in Brazil - a country in which a pro-rata method (which does not result in location-specific economic signals) is currently used. While assessing these impacts, we focus on treatment of risk from the generators' perspective.
Capítulos en libros
Keywords: Instituto de Investigación Tecnológica (IIT)